Survey of the Properties of the Master Cartons (Corrugated Fibreboard Boxes) Used in Frozen Shrimp Industry - GOPAL, T. K SRINIVASA; GOVINDAN, T K (Fishery Technology, 2017)
Master cartons for fishery products collected from different prawn freezing factories were evaluated for bursting strength, puncture resistance, waterproofness, combined weight of liners, basis weight of the corrugating medium, weight of the carton, dimensions of the carton, wax content and saponifiable matter and discussed in the light of the ISI standards